عالم البناء السردي "في ديسمبر تنتهي كل الأحلام" لأثير عبد الله النشمي - نسيب، ايمان, طواهرية، فاطمة (جامعة الوادي University of Eloued, 2019)
تعد الرواية من أبرز الأشكال السردية التي ظهرت في الساحة الأدبية الحديثة، في الوطن العربي عامة والسعودية خاصة، وذلك لما تلامسه من قضايا المجتمع السعودي، وهذا ما يبرز البناء السردي في الرواية التي هي محض دراستنا، التي تمثلت في رواية " في ديسمبر تنتهي كل الأحلام" لأثير عبد الله النشمي. وذلك بتنوع بناء شخصياتها بحسب الأدوار التي تقتضيها الرواية من شخصيات نامية وسكونية وغائبة ومجازية، كما اعتمدت الروائية على مختلف التقنيات السردية من لواحق وسوابق، بالإضافة إلى الايقاع الزمني من حذف وخلاصة ووقفة ومشهد، أما الفضاء المكاني للرواية، فقد تمثل في الرياض ولندن ومبنى الصحيفة والشقة. ووظفت الروائية خصائص الخطاب السردي والمتمثل في اللغة والعنوان والوصف والحوار والتكرار. كل هذا ساعد في إبراز جمالية الرواية The novel is one of the most abstract forms of narrative that emerged in the modern literary scene, in the Arab world in general and in Saudi Arabia in particular, because of the Saudi society's issues. This highlights the narrative construction of the novel, which is the study of " To Atheer Abdullah Al Nashmi. And the diversity of the construction of characters according to the roles required by the novel from the characters of developing and silent and absent and miraculous, and relied on the novelist on the various techniques of narrative precedents and precedents, in addition to the temporal rhythm of the deletion and summary and pause and scene, and spatial space of the novel, were represented in Riyadh and London and the newspaper building and apartment . The novelist employed the characteristics of narrative discourse in language, title, description, dialogue and repetition. All this helped to highlight the beauty of the novel.
Keywords: بناء الشخصية، بناء الزمان والمكان، خصائص الخطاب السردي; building personality, building time and space, characteristics of narrative discourse.